Electrodialysis concentration of sulfuric acid - S. A. Loza; N. A. Smyshlyaev; A. N. Korzhov; N. A. Romanyuk (Chimica Techno Acta, 2021)
An urgent task is the development of new resource-saving technologies for deep processing of wastes from the hydrometallurgical industry for the purpose of their reuse. Membrane technologies make it possible to create closed technological cycles with the reuse of recovered components in production, which allows solving many environmental problems. At the Abinsk Electric Steel Works Ltd. (Russia), during the production of copper-coated steel wire, a large amount of waste containing sulfuric acid and heavy metal salts is generated. The chemical treatment of such effluents with slaked lime and alkali produces a large amount of sludge, which causes environmental problems and leads to the irreversible loss of sulfuric acid. The problem of separating acids and salts can be solved using diffusion dialysis through anion-exchange membranes, however, to return the acid to the production cycle, the purified acid must be additionally concentrated. In this work, we studied the process of electrodialysis concentration of sulfuric acid using heterogeneous ion-exchange membranes Ralex® CMHPP and Ralex® AMHPP (manufactured by MEGA a.s., Czech Republic) which have a polypropylene reinforcing mesh resistant to acids. The main parameters of the electrodialysis concentration process have been determined – the dependence of the concentration of the regenerated sulfuric acid on the concentration at the inlet to the electrodialysis cell and on the current density, as well as the energy consumption for the process. It is shown that with the help of electrodialysis concentration it is possible to obtain sulfuric acid with a concentration of up to 180 g/L, which makes it possible to return it to the production cycle.